Symbolika księżyca w Enarrationes in psalmos św. Augustyna - Zgraja, Brunon (Vox Patrum, 2018)
The present article proves that Augustine, explaining in Enarrationes in Psalmos the texts of Psalms, does not treat references occurig in them, to the moon merely as a part of the descriptions of beauty of the created world, but tries to perceive in it a hidden meaning, the disclosure of which serves the interpreation of different theological questions. For the bishop of Hippo, the moon is a metaphor of God the Creator, of Christ, of the Church and of the human being. With reference to God the Creator, the moon is to remind Christians, that God creating everything as being good and beautiful, He himself is the Good and the Beauty. Furthermore, the motive of the moon is to point to God’s self-sufficiency, his freedom and independence. The moon as metaphor of Christ, in turn, allows to perceive in Him the true God who, through the event of Incarnation, revealed to the human being the eternal plan of salvation. The ecclesiological dimension of the symbolism of the moon, however, introduces the concept of the beginnings of the Church, points out to its persecutions and to the presence of sinful people in it. What’s more, the moon-Church is the mystical Body of Christ and Christi s its Head. It is, furthermore, a Glorious Church that will be reigning with Christ for ever. Through the antropological dimension of the figure of the moon, Augustine exposes to the listeners of his sermons the truth about human fragility, corporality and mortality, moral inconstancy and a necessity for gaining more and more perfection with the suport of the Holy Spirit. The moon is salso to direct the human thinking at the truth of resurrection.